2017
DOI: 10.5152/tud.2017.58538
|View full text |Cite
|
Sign up to set email alerts
|

Clinical effect of discordance in empirical treatment of cases with urinary tract infection accompanied by bacteremia

Abstract: Objective: It has been shown in previous studies that inadequate empirical treatment is associated with mortality in a variety of infections caused by Gram-negative bacteria. In this study, the clinical effect of discordance in empirical treatment was investigated in patients with urinary tract infection (UTI) accompanied by bacteremia. Material and methods:We retrospectively reviewed the files of adult (>18 years old) patients who were diagnosed with UTI in our clinic between January 2014 and December 2015. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…It is possible that despite being suboptimal, an appropriate agent was ultimately used considering the susceptibility of the uropathogen causing the UTI. Three previous studies have similarly demonstrated that inappropriate empiric therapy for UTI was not associated with an increased risk of mortality [62][63][64]. Excessive treatment duration versus optimal treatment was associated with a decreased hazard of mortality.…”
Section: Discussionmentioning
confidence: 88%
“…It is possible that despite being suboptimal, an appropriate agent was ultimately used considering the susceptibility of the uropathogen causing the UTI. Three previous studies have similarly demonstrated that inappropriate empiric therapy for UTI was not associated with an increased risk of mortality [62][63][64]. Excessive treatment duration versus optimal treatment was associated with a decreased hazard of mortality.…”
Section: Discussionmentioning
confidence: 88%